2013
DOI: 10.5114/ceji.2013.34357
|View full text |Cite
|
Sign up to set email alerts
|

Experimental immunology Modulatory effects of bestatin on T and B lymphocyte subsets and the concentration of cytokines released by Th1/Th2 lymphocytes in cyclophosphamide-treated mice

Abstract: The low-molecular weight dipeptide bestatin is a potent inhibitor of aminopeptidase N and has been mg/kg five times at 48 h intervals or ten times at 24 h intervals, intraperitoneally. Immunosuppression was induced by a single injection of cyclophosphamide at a dose of 350 mg/kg. It was found that bestatin administered ten times at 24 h intervals at a dose of 1 mg/kg increased the total number of splenic lymphocytes (which was previously decreased by cyclophosphamide). Five and ten exposures to the investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that immunoregulatory selenium-enriched peptides from soybean can restore the CTX-induced decrease of WBCs [ 43 ]. Lis et al [ 44 ] revealed that a low molecular weight dipeptide bestatin significantly improved the CTX-induced decrease in the number of peripheral blood LYM. These results indicated that the administration of CBH and HD restored normal blood indices, implying that CBH and HD protect against immunosuppression induced by CTX.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that immunoregulatory selenium-enriched peptides from soybean can restore the CTX-induced decrease of WBCs [ 43 ]. Lis et al [ 44 ] revealed that a low molecular weight dipeptide bestatin significantly improved the CTX-induced decrease in the number of peripheral blood LYM. These results indicated that the administration of CBH and HD restored normal blood indices, implying that CBH and HD protect against immunosuppression induced by CTX.…”
Section: Resultsmentioning
confidence: 99%
“…In this report, the cyclophosphamideinduced immunosuppression was verified by means of cytokines production both in vitro and in vivo. In other report, cyclophosphamide-induced immune modulation changes T and B lymphocyte subsets and increases cytokines release by Th1/Th2 lymphocytes in mice model [13] . After treatment with PME, rats had better body and organs weight compared to cyclophosphamide-treated group.…”
mentioning
confidence: 79%
“…Based on the evaluation of immunity, cyclophosphamide-induced immunomodulated mice exhibited significant immune-related differences compared to untreated mice, such as reduced activity of splenocytes, and repressed productions of TNF-α, IL-2 and IL-12 in serum and in splenocytes, suggesting that cyclophosphamide is a potent immunomodulators [12,13] . Moreover spleen of normal and immunodeficient mice displayed significant changes in IFN-γ mRNA expression [14] .…”
mentioning
confidence: 99%
“…In addition, the occurrence of immune dysfunction seems to be regulated by IFN-γ and IL-4 levels, and the decrease of their levels may lead to impaired immune function 23 . Studies have shown that CYP, as an effective immunosuppressant, can induce the decrease of IFN-γ and IL-4 levels, thus destroying immune homeostasis and leading to immunosuppression 24 . It is worth noting that B. coagulans MZY531 treatment significantly increases the levels of IFN-γ and IL-4 and increases the expression of immune-related cytokines, including IgG, IgM, IgA, and IgE.…”
Section: Discussionmentioning
confidence: 99%